Recent Wireless Power Transfer Technologies - Pinho, Pedro (IntechOpen, 2020)
The Wireless Power Transfer concept is continuously and rapidly evolving and new challenges arise every day. As a result of these rapid changes, the need for up-to-date texts that address this growing field from an interdisciplinary perspective persists. This book, organized into ten chapters, presents interesting novel solutions in the exploitation of the near- and far-field techniques of wireless power transfer that will be used in the near future, as well as a bird's eye view of some aspects related to an emerging technological area that will change our lives and will change the paradigm of how we use electrical equipment. The book covers the theory and also the practical aspects of technology implementation in a way that is suitable for undergraduate and graduate-level students, as well as researchers and professional engineers.